A modified Zerilli–Armstrong model as the asymmetric visco-plastic part of a multi-mechanism model for cutting simulations - Cheng, C.; Mahnken, Rolf (Archive of Applied Mechanics)

Goal-oriented mesh adaptivity for inverse problems in linear micromorphic elasticity - Ju, X.; Mahnken, Rolf; Liang, L.; Xu, Y. (Computers & Structures)

Integral‐type non‐local damage simulation of composites using mean‐field homogenization methods - Lenz, Peter; Mahnken, Rolf (PAMM)

Physics informed neural networks for continuum micromechanics - Henkes, Alexander; Wessels, Henning; Mahnken, Rolf (PAMM)

Die technische Perspektive konkret. Begleitband 5 zum Perspektivrahmen Sachunterricht.

Zur Stärkung von Erziehungskompetenz durch Elternbildung: Entwicklungen, Programme, Ambivalenzen - Landhäußer, Sandra; Faas, Stefan; Schmidt, Thilo; von Guilleaume, Christine (Familie im Kontext kindheits- und sozialpädagogischer Institutionen)
Für weite Teile der Pädagogik der frühen Kindheit als auch der Sozialpädagogik ist die Bezugnahme auf Familie aus der Perspektive von Praxiszusammenhängen konstitutiv. Durch gesellschaftliche Ent- wicklungen gerät die Familie in Krisen, die es pädagogisch zu bearbeiten gilt. Aus (inter- und inner-)disziplinären Perspektiven versammelt der Band analytische Beiträge, die diskutieren, auf welche Weise die jeweiligen Diskurse Zustands- und Aufgabenbeschreibungen der Familie konstruieren und wie die jeweilige Verhältnisbestimmung dis- ziplinäre Gemeinsamkeiten, aber auch Abgrenzungen begründen.
Keywords: Erziehungskompetenz; Elternbildung: Entwicklungen; Programme; Ambivalenzen

Sonine Formulas and Intertwining Operators in Dunkl Theory - Rösler, Margit; Voit, Michael (International Mathematics Research Notices)
Abstract Let $V_k$ denote Dunkl’s intertwining operator associated with some root system $R$ and multiplicity $k$. For two multiplicities $k, k^{′ }$ on $R$, we study the intertwiner $V_{k^{′ },k} = V_{k^{′ }}° V_k^{-1}$ between Dunkl operators with multiplicities $k$ and $k^{′ }.$ It has been a long-standing conjecture that $V_{k^{′ },k}$ is positive if $k^{′ } ≥ k ≥ 0.$ We disprove this conjecture by constructing counterexamples for root system $B_n$. This matter is closely related to the existence of Sonine-type integral representations between Dunkl kernels and Bessel functions with different multiplicities. In our examples, such Sonine formulas do not exist. As a consequence, we obtain necessary conditions on Sonine formulas for Heckman–Opdam hypergeometric functions of type $BC_n$ and conditions for positive branching coefficients between multivariable Jacobi polynomials.
Keywords: General Mathematics

Positive intertwiners for Bessel functions of type B - Rösler, Margit; Voit, Michael (Proceedings of the American Mathematical Society)
Keywords: Applied Mathematics; General Mathematics

Die Rolle inter- und intraindividueller Erfahrungen für die Einstellungen von Grundschulkindern gegenüber Peers mit emotional-sozialem Förderbedarf. Vortrag auf der 56. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung“ - Löper, Marwin Felix; Schwab, Susanne; Lehofer, Mike; Hellmich, Frank

Selbstwirksamkeitsüberzeugungen von Primarstufenlehrkräften im Kontext schulischer Inklusion – Eine Untersuchung potenzieller Prädiktoren. Vortrag auf der 56. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung“ - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

Handlungsintentionen bei der Gestaltung adaptiven Unterrichts – Ein Vergleich zwischen Lehrkräften an inklusiven und nicht- inklusiven Grundschulen. Vortrag auf der 56. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung“ - Löper, Marwin Felix; Hellmich, Frank

Bedingungen für die erfolgreiche Umsetzung von Inklusion aus Sicht von Schulleitungen an Grundschulen. Vortrag auf der 56. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung“ - Görel, Gamze; Hellmich, Frank

The quality of student-teacher relationship and teachers’ behaviour as predictors for children’s attitudes towards peers with learning disabilities. Single Paper. ECER 2021 (European Conference on Educational Research). “Education and Society: expectations, prescriptions, reconciliations” - Löper, Marwin Felix; Hellmich, Frank

Differentiation and individualisation as key features of inclusive teaching quality – Findings from a qualitative study with primary school teachers. Single Paper. ECER 2021 (European Conference on Educational Research). “Education and Society: expectations, prescriptions, reconciliations” - Görel, Gamze; Hellmich, Frank

The promotion of pre-service teachers’ team-teaching competencies for inclusive education. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Hellmich, Frank; Schulze, Jan Roland; Hoya, Fabian Karl

Sources of primary school teachers’ self-efficacy to teach in inclusive classrooms. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Franzen, Katja; Hellmich, Frank; Moschner, Barbara

Prospektive und prozessbezogene Kompetenzanalyse im Digitalisierungskontext – Gestaltung und Erprobung eines Vorgehens - Depenbusch, Sarah; Bender, Elena; Schaper, Niclas (Zeitschrift für Arbeitswissenschaft)
Zusammenfassung Im Zuge der Digitalisierung von Arbeits- und Geschäftsprozessen ist es wichtig, Kompetenzanforderungen zukunftsbezogen und konkret zu ermitteln, um Entwicklungsbedarfe frühzeitig zu erkennen. Dieser Beitrag untersucht daher, wie zukünftige Kompetenzen zugleich prospektiv und prozessbezogen erfasst werden können. Dazu wird ein Vorgehen erprobt, welches verschiedene Verfahren der Anforderungsanalyse integriert. In der gegenwartsbezogenen Analysephase werden zunächst die Kompetenzen ermittelt, die für den Prozess vor dessen digitaler Veränderung relevant sind, und in gegenwarts- und prozessbezogenen Kompetenzprofilen zusammengefasst. In der zukunftsbezogenen Analysephase werden anschließend die für den veränderten, digitalisierten Prozess erforderlichen Kompetenzen hergeleitet und in zukunfts- und prozessbezogenen Kompetenzprofilen abgebildet. Die Kompetenzerhebung erfolgt in beiden Analysephasen mittels Experteninterviews, in denen dieselben Befragungsinstrumente eingesetzt werden. Durch einen Vergleich der gegenwarts- und zukunftsbezogenen Kompetenzprofile lassen sich schließlich zukünftige Kompetenzentwicklungsbedarfe der Mitarbeitenden prozessbezogen und prospektiv ableiten. Praktische Relevanz : Das Vorgehen ermöglicht Unternehmen die prospektive und prozessbezogene Erfassung zukünftig relevanter Kompetenzen und Entwicklungsbedarfe sowie die Gestaltung individueller und prozessorientierter Kompetenzentwicklungsmaßnahmen, insbesondere im Digitalisierungskontext. Die prospektive Ableitung des zukünftigen Entwicklungsbedarfs ist wichtig, um technologisch mit dem digitalen Wandel Schritt zu halten und die Mitarbeitenden dabei proaktiv mit einzubeziehen.

Work Characteristics or Workers’ Characteristics? An Input-Process-Output Perspective on Informal Workplace Learning of Blue Collar Workers. - Decius, Julian; Schaper, Niclas; Seifert, Andreas (Vocations and Learning)

Bildungswissenschaftliches Wissen und Kompetenzselbsteinschätzungen unter Berücksichtigung individueller Voraussetzungen. Ergebnisse der Befragung angehender Lehrkräfte im Praktikum. - Seifert, Andreas; Caruso, Carina (PraxisForschungLehrer*innenBildung. Zeitschrift für Schul- und Professionsentwicklung.)

„Allgemein hat sich die psychische Gesundheit vieler Schüler verschlechtert…” – Belastungserleben als Herausforderung von Abiturientinnen und Abiturienten im digital vermittelten Distanzunterricht. - Rogge, Tm; Seifert, Andreas (DigiGebf21)

„Ich weiß die Antwort nicht“ – Ein Mangel an Motivation oder ein Mangel an Wissen? - Watson, Christina; Seifert, Andreas (PAEPSY 2021)

All-Optical Beam Steering Using the Polariton Lighthouse Effect - Luk, Samuel M. H.; Vergnet, Hadrien; Lafont, Ombline; Lewandowski, Przemyslaw; Kwong, Nai H.; Galopin, Elisabeth; Lemaitre, Aristide; Roussignol, Philippe; Tignon, Jérôme; Schumacher, Stefan; Binder, Rolf; Baudin, Emmanuel (ACS Photonics)

Chancen des inklusionsorientierten Sachunterrichts für didaktisch-diagnostisches Handeln. Konzeptionelle und methodologisch-methodische Grundlagen eines forschungsbasierten Entwicklungsansatzes für die Lehrer*innenbildung - Schroeder, René; Blumberg, Eva; Kottmann, Brigitte; Miller, Susanne; Reh, Anne (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
In der Herausforderung Unterricht inklusionsbezogen weiterzuentwickeln, manifestiert sich unter anderem die Forderung nach der Qualifizierung von (angehenden) Lehrkräften bzgl. der Anwendung und Umsetzung einer alltagsintegrierten Diagnostik mit dem Ziel, Kinder individualisiert und gleichzeitig mit Bezug auf einen gemeinsamen Lerngegenstand zu unterrichten. Dabei ist ein didaktisch-diagnostisches Handeln aller Lehrkräfte gefordert, welches im Kontext einer professionellen und inklusionsorientierten Gestaltung sowie einer angemessenen Begleitung und Förderung von Lern- und Entwicklungsprozessen steht. In der Konzeption entsprechender Aus- und Weiterbildungsformate setzt das geplante Projekt DiPoSa (Didaktisch-diagnostische Potentiale des inklusionsorientierten Sachunterrichts) an. Ziel ist es durch einen Design-Based-Research-Ansatz (DBR) Videovignetten zu erstellen und zu evaluieren, mittels derer entsprechende Kompetenzen von (angehenden) Lehrkräften im Sachunterricht weiterentwickelt werden können. Dabei bietet insbesondere der Sachunterricht als vielperspektivisches Integrationsfach der Grundschule einen passenden Rahmen, kindliche Lernpotentiale als Ausgangspunkt für didaktisch-diagnostisches Handeln nutzbar zu machen. Denn in aktuellen inklusionsorientierten Ansätzen des Sachunterrichts sind sowohl reformpädagogisch orientierte als auch offene Konzepte und Modelle des adaptiven Unterrichts zu finden, die sich an den unterschiedlichen Programmatiken der Umsetzung von individueller Förderung orientieren. Im folgenden Beitrag werden die dem geplanten Projekt zugrundeliegenden theoretischen und empirischen Zugänge erläutert und die forschungsmethodische Umsetzung durch einen DBR-Ansatz als methodologische Basis für eine Theorie-Praxis-verzahnende Forschungsperspektive auf diagnostisches Handeln sowie die Förderung diagnostischer Handlungskompetenzen durch Videovignetten im Kontext der Aus- und Weiterbildung von (Sachunterrichts-)Lehrkräften diskutiert. Abstract The challenge to further promote practices of inclusive teaching, requires the development of assessment literacy. Combined with the aim to teach all children in a collaborative learning environment, qualification of teachers (in training) in the application and implementation of formative assessment as an integrated daily routine is needed. Therefore, the project DiPoSa focuses on the development of appropriate training and qualification formats. The project heads to create and evaluate video vignettes using a design-based-research approach (DBR), which can then be used to further develop assessment literacy of teachers in social studies and science in primary education. As a multi-perspective integrative subject in elementary school social studies and science in primary education offers a suitable framework for practices of formative assessment taking children's learning potentials as a serious concern. Foundations can be seen in current inclusive approaches to social studies and science in primary education, where reform pedagogically orientation and open concepts can as well be found as models of adaptive teaching. Although there are different theoretical and programmatic implementations, both perspectives share an orientation towards individual support of children. With this in mind the following article tries to lay down the theoretical and empirical approaches of the planed project DiPoSa and discusses methodological foundations of the project. The discussion focuses on how assessment practices as well as assessment literacy can be promoted through a DBR research-design using video vignettes in the context of teacher education and qualification and rooting in a deepened science-practice partnership.Zusammenfassung englisch
Keywords: General Medicine

Microscopic Insights into Charge Formation and Energetics in n-Doped Organic Semiconductors - Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Kooperatives Lernen von Lehramtsstudierenden im Zusammenhang mit ihrer Qualifizierung für den inklusiven naturwissenschaftlichen Sachunterricht der Grundschule – Ergebnisse aus dem Forschungsprojekt. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne

The impact of the composition of pre-service teacher teams on children’s competencies in (non-)inclusive primary school science lessons. Single Paper. ECER 2021 (European Conference on Educational Research). “Education and Society: expectations, prescriptions, reconciliations” - Hellmich, Frank; Schulze, Jan Roland; Blumberg, Eva; Hoya, Fabian Karl

Marktmachtmissbrauch digitaler Plattformen - eine Analyse anhand der zehnten Novelle des GWB - Kanne, Niklas

Marktmachtmissbrauch von Google – Eine wettbewerbspolitische Analyse - Klüppel, Pascal

Lernen, die Welt zu verändern. Einblick aus Wissenschaft und Praxis zur Verankerung von BNE im Schulprofil – am Beispiel des Frei-Day. Podcast-Beitrag am 7. Münsterschen Bildungskongress mit LemaS-Jahrestagung. Online - Büker, Petra; Rasfeld, Margret; Feitkenhauer, Tobias; Boos, Mareike
September 2021

Paderborner Qualitätsstern (PQ³) zur Einschätzung der Kooperation im Übergang Kita – Grundschule. Ein Selbstevaluationsinstrument für multiprofessionelle und institutionsübergreifende Zusammenarbeit - Höke, Julia; bö, Petra (Diskurs Kindheits- und Jugendforschung/Discourse. Journal of Childhood and Adolescence Research)

Laser-carbonization: Peering into the formation of micro-thermally produced (N-doped)carbons - Wang, Huize; Delacroix, Simon; Osswald, Oliver; Anderson, Mackenzie; Heil, Tobias; Lepre, Enrico; Lopez Salas, Nieves; Kaner, Richard B.; Smarsly, Bernd; Strauss, Volker (Carbon)
Keywords: General Chemistry; General Materials Science

Caffeine-Derived Noble Carbons as Ball Milling-Resistant Cathode Materials for Lithium-Ion Capacitors - Ilic, Ivan K.; Lepre, Enrico; Lopez Salas, Nieves (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Carbonaceous Materials: The Beauty of Simplicity - Lopez Salas, Nieves; Antonietti, Markus (Bulletin of the Chemical Society of Japan)
Keywords: General Chemistry

Sustainable oxidation catalysis supported by light: Fe-poly (heptazine imide) as a heterogeneous single-atom photocatalyst - da Silva, Marcos A.R.; Silva, Ingrid F.; Xue, Qi; Lo, Benedict T.W.; Tarakina, Nadezda V.; Nunes, Barbara N.; Adler, Peter; Sahoo, Sudhir K.; Bahnemann, Detlef W.; Lopez Salas, Nieves; Savateev, Aleksandr; Ribeiro, Caue; et al. (Applied Catalysis B: Environmental)
Keywords: Process Chemistry and Technology; General Environmental Science; Catalysis

PtRu nanoparticles supported on noble carbons for ethanol electrooxidation - Rodríguez-Gómez, Alberto; Lepre, Enrico; Sánchez-Silva, Luz; Lopez Salas, Nieves; de la Osa, Ana Raquel (Journal of Energy Chemistry)
Keywords: Electrochemistry; Energy (miscellaneous); Energy Engineering and Power Technology; Fuel Technology

Politisch? Poetisch? Persönlich? Barbara Strozzis „Il lamento“ zwischen Selbstausdruck und politischer Positionierung - Tumat, Antje (Barbara Strozzi)

Pädagogische Handlungskonzepte in Kinderladenbewegung und Elterninitiativen - Bock, Karin; Göddertz, Nina (Frühpädagogische Handlungskonzepte. Eine wissenschaftliche Bestandsaufnahme.)
Im Folgenden geht es um das pädagogische Handlungskonzept bzw. genauer: ‚päda-go gische Handlungskonzepte einer Erziehung, die als „antiautoritär“ in der Fach-literatur‘ bezeichnet wird (z. B. Rabe-Kleberg, 1993). Diese Bezeichnung, die wir bis heute in Handbüchern, Lexika und Sammelbänden fi nden, geht u. a. auf den bundes-republikanischen Entstehungskontext der 1960er und 1970er Jahre zurück, einer Zeit, die von internationalen politisch-sozialen (Reform-)Bewegungen und Protesten ge-prägt war, allen voran der Studenten-, der Frauen- und der Kinderladenbewegung. Alle drei Bewegungen waren u. a. getragen von der Idee, dass mit einer repressions-freien, selbstregulierenden, an demokratischen Grundlagen und an den Bedürfnissen des Kindes ausgerichteten Erziehung die ‚Sinnentleerung kapitalistisch-autoritär ge-prägter Verhältnisse‘1 überwunden werden könn(t)e (z. B. Aden-Grossmann, 2011).Insoweit müssen die Antworten auf die Frage nach den pädagogischen Hand-lungskonzepten im Kontext von Kinderladenbewegung und Elterninitiativen eng mit den gesellschaft lichen, politischen und sozialen Ereignissen dieser Zeit verknüpftwerden, da insbesondere die ‚politischen Kämpfe‘ gegen die damals geltenden (autori-tären) politischen Ereignisse Auslöser der Idee einer ‚ antiautoritären Erziehung‘ waren, u. a. die Auswirkungen des Atombombenabwurfs über Hiroshima sowie der ‚Sputnikschock‘ in den 1950er Jahren, der sog. ‚Vietnamkrieg‘ der USA, die Nicht-Aufarbeitung des deutschen Nationalsozialismus, die Notstandsgesetze in der BRD, u. a. politische Entwicklungen rund um den Globus im Horizont des ‚Kalten Krieges‘, die sich als para- und direkt militärisch mit autoritärem Grundcharakter auszuweiten drohten (ausführlicher z. B. Vinen, 2018). Daher werden wir im vorliegenden Beitrag versuchen, über einen historischen Zugang den Bogen von der Kinderladenbewegung als Teil der Neuen Sozialen Be-wegungen rund um 1968 in Westdeutschland über Kernaussagen, pädagogische Grundsätze und paradigmatische Grundannahmen bis hin zur Einordnung in aktuelle Forschungsbefunde zu Kinderläden und sog. Elterninitiativen bzw. Elterninitiativ-Kitas (auch „EI-Kitas“, Aden-Grossmann, 2011, S. 153) aufzuspannen. Vorausgeschickt sei, dass der Forschungsstand über die pädagogischen Handlungskonzepte im Kontext von Kinderladenbewegung und Elterninitiativen nach wie vor unübersichtlich und lückenhaft ist, von Mythen, Gründungsgeschichten und allerlei ‚Erzählungen‘ ge-tragen, aber deshalb umso interessanter, weil er nicht nur selbstverständliche Gewiss-heiten, sondern auch viele off ene Fragen bereithält.
Keywords: Pädagogik; Erziehungswissenschaft

Digitale Lehr-Lern-Räume in der beruflichen Fachrichtung Sozialpädagogik - Göddertz, Nina; Karber, Anke (Care Work 4.0)
Einhergehend mit der Digitalisierung – verschärft in Zeiten der Covid19-Pandemie – zeigen sich strukturelle wie didaktische Herausforderungen für Universitäten, Leh- rende und Studierende, denen auch die Didaktik der Sozialpädagogik begegnen muss. Mit dem vorliegenden Beitrag wird in Anknüpfung an den klassischen sozial- pädagogischen Ansatz der Lebensweltorientierung (Hans Thiersch) die Weiterent- wicklung einer fachgebundenen Hochschuldidaktik der (Berufsschul-)Lehrer:innen- bildung der Fachrichtung Sozialpädagogik angestoßen.
Keywords: Berufliche Bildung; Didaktik der Sozialpädagogik; fachgebundene Hochschuldidaktik; Lebensweltorientierung

»Stilistik« - Schuster, Britt-Marie (Text- und Diskurslinguistik)

»Abweichung« - Schuster, Britt-Marie (Text- und Diskurslinguistik)

»abweichen« - Schuster, Britt-Marie (Text- und Diskurslinguistik)

Data Science ab Klasse 5–Konkrete Unterrichtsvorschläge für künstliche Intelligenz unplugged und Datenbewusstsein - Podworny, Susanne; Höper, Lukas; Fleischer, Yannik; Hüsing, Sven; Schulte, Carsten (INFOS 2021–19. GI-Fachtagung Informatik und Schule)

Zur neuen Bedeutung von Daten in Data Science und künstlicher Intelligenz - Höper, Lukas; Podworny, Susanne; Hüsing, Sven; Schulte, Carsten; Fleischer, Yannik; Biehler, Rolf; Frischemeier, Daniel; Malatyali, Hülya (INFOS 2021–19. GI-Fachtagung Informatik und Schule)

TA und Zeitdiagnosen. TA als Zeitdiagnose? - Alpsancar, Suzana (Technikfolgenabschätzung. Handbuch für Wissenschaft und Praxis)

Epiphanias 06.01.2022. Joh 1,15-18: Ende vom Lied: Gnade um Gnade - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien IV/1)

Laienbewegung. Zur Produktivität einer für den Protestantismus unsauberen ekklesiologischen Kategorie - Schroeter-Wittke, Harald (Volkskirche in postsäkularer Zeit. Erkundungsgänge und theologische Perspektiven. Kristian Fechtner zum 60. Geburtstag)

Magdalene Schauss-Flake (1921-2008). Gebrauchsmusik als Religionspädagogik - Schroeter-Wittke, Harald (Musikwissenschaft als Vielfalt. Festschrift für Rebecca Grotjahn zum 60. Geburtstag)

Reinold von Thadden-Trieglaff. Der Zusammenführer - Schroeter-Wittke, Harald (Protestantische Impulse. Prägende Gestalten in Deutschland nach 1945)

Es ist ein Ros entsprungen. Zum 400. Todestag von Michael Praetorius (1571/72-1621) - Schroeter-Wittke, Harald (Praktische Theologie)

Das Kirchentagszeichen. Zum 100. Geburtstag von Magdalene Schauss-Flake - Schroeter-Wittke, Harald (Praktische Theologie)

Zwischen Muezzin und Kathedrale. Der Traum vom Mittelmeer als Musik - Schroeter-Wittke, Harald (Praktische Theologie)

Alles ist Musik! – „Wir bräuchten da mal was.“ Zum 100. Geburtstag von Magdalene Schauss-Flake (1921-2008) - Schroeter-Wittke, Harald; Schmidt-Eggert, Friedemann (Posaunenchor. Magazin für Bläserinnen und Bläser)

Erzählte Modegeschichte – Interviews mit Zeitzeugen des Couturiers Werner Lauer. In: nmt 2020 – Mode und Textil - Haller, Melanie (Netzwerk Mode und Textil, 2021 (Peer Reviewed))

Iron oxide catalysts for CO oxidation : from basic structure-activity-correlation to an advanced preparation strategy for highly active catalysts - Schlicher, Steffen

Der Weg zur Gewalt – Ein zwischenzuständliches Gespräch über Dumpfbacken, Depressionen und Druckwellen. - Jacke, Christoph (Kaput - Magazin für Insolvenz & Pop)

COVID-19 Reporting and Willingness to Pay for Leisure Activities - Ortmann, Regina; Warkulat, Sonja; Krull, Sebastian; Klocke, Nina; Pelster, Matthias

Real effects of an international tax reform for MNEs - Ortmann, Regina; Simons, Dirk; Voeller, Dennis

Optical Arbitrary Waveform Measurement Using Silicon Photonic Slicing Filters - Fang, Dengyang; Zazzi, Andrea; Müller, Juliana; Dray, Daniel; Fullner, Christoph; Marin-Palomo, Pablo; Tabatabaei Mashayekh, Alireza; Dipta Das, Arka; Weizel, Maxim; Gudyriev, Sergiy; Freude, Wolfgang; Randel, Sebastian; et al. (Journal of Lightwave Technology)
We demonstrate an optical arbitrary waveform measurement (OAWM) system that exploits a bank of silicon photonic (SiP) frequency-tunable coupled-resonator optical waveguide (CROW) filters for gapless spectral slicing of broadband optical signals. The spectral slices are coherently detected using a frequency comb as a multi-wavelength local oscillator (LO) and stitched together by digital signal processing (DSP). For high-quality signal reconstruction, we have implemented a maximum-ratio combining (MRC) technique based on precise calibration of the complex-valued opto-electronic transfer functions of all detection paths. In a proof-of-concept experiment, we demonstrate the viability of the scheme by implementing a four-channel system that offers an overall detection bandwidth of 140 GHz. Exploiting a femtosecond laser with precisely known pulse shape for calibration along with dynamic amplitude and phase estimation, we reconstruct 100 GBd QPSK, 16QAM and 64QAM optical data signals. The reconstructed signals show improved quality compared to that obtained with a single high-speed intradyne receiver, while the electronic bandwidth requirements of the individual coherent receivers are greatly reduced.
Keywords: Atomic and Molecular Physics; and Optics

Optically Enabled ADCs and Application to Optical Communications - Zazzi, Andrea; Müller, Juliana; Weizel, Maxim; Koch, Jonas; Fang, Dengyang; Moscoso-Martir, Alvaro; Tabatabaei Mashayekh, Ali; Das, Arka D.; Drays, Daniel; Merget, Florian; Kartner, Franz X.; Pachnicke, Stephan; et al. (IEEE Open Journal of the Solid-State Circuits Society)
Electrical-optical signal processing has been shown to be a promising path to overcome the limitations of state-of-the-art all-electrical data converters. In addition to ultra-broadband signal processing, it allows leveraging ultra-low jitter mode-locked lasers and thus increasing the aperture jitter limited effective number of bits at high analog signal frequencies. In this paper, we review our recent progress towards optically enabled time- and frequency-interleaved analog-to-digital converters, as well as their monolithic integration in electronic-photonic integrated circuits. For signal frequencies up to 65 GHz, an optoelectronic track-and-hold amplifier based on the source-emitter-follower architecture is shown as a power efficient approach in optically enabled BiCMOS technology. At higher signal frequencies, integrated photonic filters enable signal slicing in the frequency domain and further scaling of the conversion bandwidth, with the reconstruction of a 140 GHz optical signal being shown. We further show how such optically enabled data converter architectures can be applied to a nonlinear Fourier transform based integrated transceiver in particular and discuss their applicability to broadband optical links in general.

Sprachwissenschaft und Fremdsprachendidaktik: Konstruktionen und Konstruktionslernen.

Confinement Effects for Efficient Macrocyclization Reactions with Supported Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes - Ziegler, Felix; Kraus, Hamzeh; Benedikter, Mathis J.; Wang, Dongren; Bruckner, Johanna R.; Nowakowski, Michal; Weißer, Kilian; Solodenko, Helena; Schmitz, Guido; Bauer, Matthias; Hansen, Niels; Buchmeiser, Michael R. (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Fundamental Characterization, Photophysics and Photocatalysis of a Base Metal Iron(II)‐Cobalt(III) Dyad - Huber‐Gedert, Marina; Nowakowski, Michał; Kertmen, Ahmet; Burkhardt, Lukas; Lindner, Natalia; Schoch, Roland; Herbst‐Irmer, Regine; Neuba, Adam; Schmitz, Lennart; Choi, Tae‐Kyu; Kubicki, Jacek; Gawelda, Wojciech; et al. (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Rh(I)/(III)‐N‐Heterocyclic Carbene Complexes: Effect of Steric Confinement Upon Immobilization on Regio‐ and Stereoselectivity in the Hydrosilylation of Alkynes - Panyam, Pradeep K. R.; Atwi, Boshra; Ziegler, Felix; Frey, Wolfgang; Nowakowski, Michal; Bauer, Matthias; Buchmeiser, Michael R. (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Immobilized Platinum Hydride Species as Catalysts for Olefin Isomerizations and Enyne Cycloisomerizations - Maier, Sarah; Cronin, Steve P.; Vu Dinh, Manh-Anh; Li, Zheng; Dyballa, Michael; Nowakowski, Michal; Bauer, Matthias; Estes, Deven P. (Organometallics)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry

Ni-Based Electrocatalysts for Unconventional CO2 Reduction Reaction to Formic Acid - Albero, Josep; Lepre, Enrico; Heske, Julian; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo Zizak; Heil, Tobias Heil; D. Kühne, Thomas; Antonietti, Markus; López-Salas, Nieves (Proceedings of the International Conference on Frontiers in Electrocatalytic Transformations)

A fully cross-diffusive two-component evolution system: Existence and qualitative analysis via entropy-consistent thin-film-type approximation. - Tao, Youshan; Winkler, Michael (Journal of Functional Analysis)

The dampening role of large repulsive convection in a chemotaxis system modeling tumor angiogenesis. - Tao, Youshan; Winkler, Michael (Nonlinear Analysis, Theory, Methods and Applications)

Immediate regularization of measure-type population densities in a two-dimensional chemotaxis system with signal consumption. - Wang, Yulan; Winkler, Michael; Xiang, Zhaoyin (Science China Mathematics)

Small-density solutiions in Keller-Segel systems involving rapidly decaying diffusivities. - Ding, Mengyao; Winkler, Michael (Nonlinear Differential Equatiions and Applicatiions)

Global smooth solutions in a two-dimensional cross-diffusion system modeling propagation of urban crime. - Tao, Youshan; Winkler, Michael (Communications in Mathematical Sciences)

Taxis-driven formation of singular hotspots in a May-Nowak type model for virus infection. - Tao, Youshan; Winkler, Michael (SIAM Journal on Mathematical Analysis)

Local energy estimates and global solvability in a threee-dimensional chemotaxis-fluid system with prescribed signal on the boundary. - Wang, Yulan; Winkler, Michael; Xiang, Zhaoyin (Communications in Partial Differential Equations)

Global solvability in a threee-dimensional Keller-Segel.Stokes system involving arbitrary superlinear logistic degradation - Wang, Yulan; Winkler, Michael; Xiang, Zhaoyin (Advances in Nonlinear Analysis)

Critical mass for infinite-time blow-up in a haptotaxis system with nonlinear zero-order interaction - Tao, Youshan; Winkler, Michael (Discrete and Continuous Dynamical Systems)

„Vom Fahr-Zeug zum Fahr-Ding. Ein Heideggerianischer Kommentar zum autonomen Automobil“ - Alpsancar, Suzana (Autonome Autos – Die Zukunft des Verkehrs und die Dispositive der Mobilität)

Building, emptying out, or dreaming? Action structures and space in students’ metaphors of academic writing - Scharlau, Ingrid; Karsten, A.; Rohlfing, Katharina J. (Journal of Writing Research)
Keywords: Literature and Literary Theory; Linguistics and Language; Language and Linguistics; Education

Comparing the Effects of a Different Social Partner (Social Robot vs. Human) on Children's Social Referencing in Interaction - Tolksdorf, Nils Frederik; Crawshaw, Camilla E.; Rohlfing, Katharina J. (Frontiers in Education)
Social robots have emerged as a new digital technology that is increasingly being implemented in the educational landscape. While social robots could be deployed to assist young children with their learning in a variety of different ways, the typical approach in educational practices is to supplement the learning process rather than to replace the human caregiver, e.g., the teacher, parent, educator or therapist. When functioning in the role of an educational assistant, social robots will likely constitute a part of a triadic interaction with the child and the human caregiver. Surprisingly, there is little research that systematically investigates the role of the caregiver by examining the ways in which children involve or check in with them during their interaction with another partner — a phenomenon that is known as social referencing. In the present study, we investigated social referencing in the context of a dyadic child–robot interaction. Over the course of four sessions within our longitudinal language-learning study, we observed how 20 pre-school children aged 4–5 years checked in with their accompanying caregivers who were not actively involved in the language-learning procedure. The children participating in the study were randomly assigned to either an interaction with a social robot or a human partner. Our results revealed that all children across both conditions utilized social referencing behaviors to address their caregiver. However, we found that the children who interacted with the social robot did so significantly more frequently in each of the four sessions than those who interacted with the human partner. Further analyses showed that no significant change in their behavior over the course of the sessions could be observed. Findings are discussed with regard to the caregiver's role during children's interactions with social robots and the implications for future interaction design.

Do Shy Children Keep more Distance from a Social Robot? Exploring Shy Children’s Proxemics with a Social Robot or a Human - Tolksdorf, Nils Frederik; Viertel, Fanziska E.; Crawshaw, Camilla E.; Rohlfing, Katharina J. (Interaction Design and Children)

Nonlinear waveguides for integrated quantum light source - Domeneguetti, Renato R.; Conradi, Hauke; Kleinert, Moritz; Kießler, Christian; Stefszky, Michael; Herrmann, Harald; Silberhorn, Christine; Andersen, Ulrik L.; Neergaard-Nielsen, Jonas Schou; Gehring, Tobias (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference)
We experimentally investigate the generation of continuous-wave optical squeezing from a titanium-indiffused lithium niobate waveguide resonator at low and high frequencies. The device promises integration with different platform chips for more complex optical systems.
Keywords: Optical systems; Polymer waveguides; Quantum key distribution; Quantum light sources; Squeezed states; Waveguides

Lehrerkooperation und Digitalisierung - Gestaltung digital-kooperativer Arbeitsbeziehungen von Lehrkräften und ReferendarInnen am Beispiel des Schulfachs Pädagogik - Engemann, M.; Herzig, Bardo (Fachliche Bildung und digitale Transformation - Fachdidaktische Forschung und Diskurse. Fachtagung der Gesellschaft für Fachdidaktik 2020)

Prospektive und prozessbezogene Kompetenzanalyse - Gestaltung und Erprobung eines Vorgehens - Depenbusch, Sarah; Bender, Elena; Schaper, Niclas

Investigating the multidimensionality of informal learning: Validation of a short measure for white‐collar workers - Decius, Julian; Knappstein, Michael; Schaper, Niclas; Seifert, Andreas (Human Resource Development Quarterly)
Keywords: Organizational Behavior and Human Resource Management; Arts and Humanities (miscellaneous)

The Hen-Egg-Problem of Informal Workplace Learning & Work Design: The Mediating Role of Job Crafting. - Decius, Julian; Schaper, Niclas; Seifert, Andreas (Academy of Management Prodeedings)

Seismograf Pop - Jacke, Christoph; Roenneke, Stefanie; Göymen, Cigdem (Pop-Musik*)

Multimode integrated SU(1,1) interferometer - Ferreri, A.; Santandrea, Matteo; Stefszky, Michael; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine; Sharapova, Polina (Conference on Lasers and Electro-Optics)
We present a frequency multimode integrated SU (1,1) interferometer with a polarization converter and strong signal-idler photon correlations. Phase sensitivity below the shot noise limit is demonstrated, various filtering and seeding strategies are discussed.

Sachunterricht lehren in Zeiten der Pandemie – Eine Online-Befragung zu den Auswirkungen der digitalen Lehre auf den Materialeinsatz und die Selbstwirksamkeitserwartungen von Lehrenden in der Sachunterrichtsdidaktik an drei deutschen Hochschulstandorten. Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Thonemann, Lisa; Reh, Anne; Deutschen, Katrin; Lakemeyer, Jana Marie; Blumberg, Eva

Digitales Sachunterrichtsstudium in der Corona-Krise – Eine empirische Evaluationsstudie zur Rezeption des analogen und webbasierten Unterstützungsangebots des Paderborner Lernzentrums „Sachunterrichtstreff“ bei Sachunterrichtsstudierenden im Grund- und Förderschullehramt. Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Deppe, Franziska; Reh, Anne; Blumberg, Eva

Voraussetzungen bei Sachunterrichtsstudierenden zum Herausforderungsbereich Digitalisierung in Schule und Hochschule – Eine empirische Online-Befragung bei Lehramtsstudierenden an Grundschulen und für sonderpädagogische Förderung. Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Brenke, Laurien; Blumberg, Eva

Einsatz digitaler Medien im Sachunterricht – Die Coronakrise als Spiegel für die fehlende Digitalisierung im deutschen Bildungswesen? Was können wir von Schweden lernen? Vortrag auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Sicking, Annika; Blumberg, Eva

Digital gestütztes Lernen im naturwissenschaftlichen Sachunterricht? Eine kriteriengeleitete Analyse digitaler sachunterrichtsbezogener Lernangebote. Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Stump, Martin; Blumberg, Eva

Prozessmodell Generative Unterrichtsplanung Sachunterricht (GUS). Posterpräsentation auf der 30. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) an der Universität Paderborn (aufgrund des pandemiebedingten digitalen Tagungsformats entfallen) - Tänzer, Sandra; Lauterbach, Roland; Blumberg, Eva; Grittner, Frauke; Lange, Jochen; Schomaker, Claudia

transMINT4.0 – Grenzen überwinden, MINT-Bildung verbinden durch außerschulische Lernorte und den Einsatz digitaler Medien. Eingeladener digital synchroner Vortrag in der MINT-Aktionswoche von MINTvernetzt - Blumberg, Eva; Schulze, Jan Roland; Temmen, Katrin; Schäfers, Johannes

Preisabsprachen in der Automobilindustrie - eine wettbewerbspolitische Analyse - Yigitbas , Osman

Facebooks digitale Währung - eine wettbewerbspolitische Analyse - Schulte, Marcel

Faszination 3D-Film: Entwicklung einer 3D-Konstruktion - Hüsing, Sven; Weiser, Niklas; Biehler, Rolf (mathematik lehren)

Der Beruf Grundschullehrer*in: Zukunftsfragen. Podcast im Rahmen der Reihe „Zukunftsgespräche“ der Peter Gläsel Stiftung - Büker, Petra
März 2021 https://pg-stiftung.net/zukunftsgespraeche/

Children as (Co)Researchers as an Opportunity to influence School Life: A Didactic Approach and its Relevance in the Perspective of Children. Beitrag im Rahmen des Symposiums: Participation to Connect Members of the School Community an der ECER (European Conference on Educational Research), University of Geneva. Online - Büker, Petra; Hüpping, Birgit
September 2021

Partizipation als Veränderung. Eine Aufforderung an Grundschule und Forschung - Büker, Petra; Hüpping, Birgit; Zala-Mezö, Enikö (Zeitschrift für Grundschulforschung)

Simulation of Guided Waves in Cylinders Subject to Arbitrary Boundary Conditions Using the Scaled Boundary Finite Element Method - Itner, D.; Gravenkamp, H.; Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd (14th WCCM-ECCOMAS Congress)

CxNy: New Carbon Nitride Organic Photocatalysts - Lopez Salas, Nieves; Albero, Josep (Frontiers in Materials)
The search for metal-free and visible light-responsive materials for photocatalytic applications has attracted the interest of not only academics but also the industry in the last decades. Since graphitic carbon nitride (g-C 3 N 4 ) was first reported as a metal-free photocatalyst, this has been widely investigated in different light-driven reactions. However, the high recombination rate, low electrical conductivity, and lack of photoresponse in most of the visible range have elicited the search for alternatives. In this regard, a broad family of carbon nitride (C x N y ) materials was anticipated several decades ago. However, the attention of the researchers in these materials has just been awakened in the last years due to the recent success in the syntheses of some of these materials (i.e., C 3 N 3 , C 2 N, C 3 N, and C 3 N 5 , among others), together with theoretical simulations pointing at the excellent physico-chemical properties (i.e., crystalline structure and chemical morphology, electronic configuration and semiconducting nature, or high refractive index and hardness, among others) and optoelectronic applications of these materials. The performance of C x N y , beyond C 3 N 4 , has been barely evaluated in real applications, including energy conversion, storage, and adsorption technologies, and further work must be carried out, especially experimentally, in order to confirm the high expectations raised by simulations and theoretical calculations. Herein, we have summarized the scarce literature related to recent results reporting the synthetic routes, structures, and performance of these materials as photocatalysts. Moreover, the challenges and perspectives at the forefront of this field using C x N y materials are disclosed. We aim to stimulate the research of this new generation of C x N y -based photocatalysts, beyond C 3 N 4 , with improved photocatalytic efficiencies by harnessing the striking structural, electronic, and optical properties of this new family of materials.
Keywords: Materials Science (miscellaneous)